A New Stripping Column Process and Optimization of Its Operation. Issue 12 (27th June 2016) - Li, Guoqing; Gao, Dan; Shi, Junjun
Abstract: Regarding a kind of stripping column that is widely used in the chemical industry and which operates in total cold reflux and without top light product, a new stripping process is suggested. It takes dual feeds of the hot plus the cold feed, by replacing part of the cold reflux with a part of cold feed, resulting in significant reduction of energy consumption and simplification of the overhead vapor route. As no changes on the column body and only a pipe are needed, this new process can be implemented conveniently in retrofitted projects. Further, an optimization study is developed for choosing the proper flow rate of the cold feed and the appropriate column running pressure. An application in a stripper dealing with the pre‐hydrotreating reaction products of an oil catalytic reformer shows that the new process is valid. Abstract : A new stripping process is suggested based on a widely used stripping column operating in total cold reflux and without top light product. By replacing part of the cold reflux with a portion of cold feed, significant energy savings and a simplified overhead vapor route are achieved. As no changes on the column body are needed, this new process can easily be implemented in retrofitted projects.